2007
DOI: 10.1016/j.jadohealth.2007.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of DSM-IV Anxiety and Depressive Disorders in Youth with Asthma Compared with Controls

Abstract: Purpose-To determine the prevalence of anxiety and depressive disorders in youth with asthma compared to a control sample of youth and to determine the sociodemographic and clinical characteristics associated with having ≥1 anxiety/depressive disorders among youth with asthma.Methods-A telephone interview was offered to all youth aged 11 to 17 with asthma (N=781) and a random sample of similar aged controls (N=598) enrolled in a Health Maintenance Organization (HMO). The C-DISC-4.0 was used to diagnose anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
159
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(175 citation statements)
references
References 39 publications
13
159
0
3
Order By: Relevance
“…However, asthma is the most common chronic disorder in youth, is responsible for high utilization of primary care and is associated with 2-fold higher rates of anxiety and depressive disorders. 17 In addition, our sensitivity analysis allowed estimation of PPV in both groups separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, asthma is the most common chronic disorder in youth, is responsible for high utilization of primary care and is associated with 2-fold higher rates of anxiety and depressive disorders. 17 In addition, our sensitivity analysis allowed estimation of PPV in both groups separately.…”
Section: Discussionmentioning
confidence: 99%
“…All youth with asthma identified via GHC automated data based on physician ICD-9 asthma diagnoses and asthma medication prescriptions were approached for interview. 17 The control sample of youth was required to have no evidence of asthma medication use or an ICD-9 diagnosis of asthma in the last 12 months. In each 4 to 6 week recruitment wave, each eligible control youth was assigned a unique number and the youth with the lowest 100 numbers were chosen.…”
Section: Subjects and Recruitmentmentioning
confidence: 99%
“…Dyspnea correlates with anxietytrait and anxiety-state, neuroticism and depression in asthmatic men [128]. Katon et al observed that youths with asthma have an almost twofold higher prevalence of comorbid anxiety and depressive disorders compared with controls [129]. In a prospective community-based cohort study of asthmatic patients followed between age 19 and 40 years, asthma was associated with anxiety and panic disorder, while after adjusting for potentially confounding variables, active asthma also predicted subsequent panic disorder [130].…”
Section: Psychopathologiesmentioning
confidence: 99%
“…The WHO estimates that there are currently 300 million people suffering from asthma and asthma is also estimated to account for ,250,000 deaths per year worldwide [12,13]. Asthma can have a significant effect on quality of life, and consequences include sleeplessness, daytime fatigue, reduced activity levels, school and work absenteeism, and mental health problems [14][15][16]. It is hypothesised that asthma is a risk factor associated with suicidal behaviour.…”
mentioning
confidence: 99%